Iron Status, Malondialdehyde, and Nitric oxide Levels in Iraqi Infertile Women with IgG Seropositive Toxoplasma Gondii - Nada A Kadhim (Journal of Global Pharma Technology, 2019)
The purpose of this study is to highlight the levels of IgG toxoplasma gondii (T. gondii) in infertile Iraqi women and its effect on iron status, malondialdehyde (MDA), and nitric oxide (NO). In order to do this, four groups were included in this study, infertile women with seropositive IgG T. gondii group (PP, n=25), infertile women with seronegative IgG T. gondii group (NP, n=25), healthy fertile women with seropositive IgG T. gondii as control group (PC, n=15) and healthy fertile women with seronegative IgG T. gondii as control group (NC, n= 15). All of the samples were tested as seronegative of IgM T. gondii. The results were as followes: Infertile women (PP) group have a significant levels of seropositive IgG T. gondii than fertile women (PC) group (P=0.008), while both (NC & NP) groups have seronegative IgG T. gondii. Serum iron and Hb concentration have been found to be with no significant differences (p>0.05), while significant increases were found in (TIBC, UIBC, transferrin and saturation of transferrin, p<0.001) in (NP vs. NC) group and (PP vs. PC) group, Also in (PP vs. NP) group and (PC vs.NC) group. The levels of malondialdehyde in serum of (NP & PP) were higher than (NC&PC) groups respectively. No remarkable changes were observed of (NC) group compared to (PC) group but a significant increase in MDA serum levels in PP group as compared to NP group, p<0.05. In addition to that levels of NO showed significant alterations in serum of infertile groups (NP & PP) as compared to that of their control groups (NC & PC) respectively (p<0.05), while no significant variation in sera of both (NP & NC) groups compared to (PP & PC) groups.Keywords: Toxoplasmosis, Infertility, Iron, Lipid peroxidation, Nitric oxide.